203k views
2 votes
What is the solution to the equation 3x+1-6x=72

User Ndifreke
by
6.0k points

2 Answers

2 votes

Answer:

=−71/3

Step-by-step explanation:3

+

1

6

=

7

2

{\color{#c92786}{3x}}+1{\color{#c92786}{-6x}}=72

3x+1−6x=72

3

+

1

=

7

2

{\color{#c92786}{-3x}}+1=72

−3x+1=72

2

Subtract

1

1

1

from both sides of the equation

3

+

1

=

7

2

-3x+1=72

−3x+1=72

3

+

1

1

=

7

2

1

-3x+1{\color{#c92786}{-1}}=72{\color{#c92786}{-1}}

−3x+1−1=72−1

3

Simplify

Subtract the numbers

Subtract the numbers

3

=

7

1

-3x=71

−3x=71

4

Divide both sides of the equation by the same term

3

=

7

1

-3x=71

−3x=71

3

3

=

7

1

3

−3−3x​=−371​

5

Simplify

Cancel terms that are in both the numerator and denominator

Divide the numbers

=−71/3

x=-\frac{71}{3}

x=−371​

User Dermot
by
6.3k points
4 votes

Answer:

hope this helps

Explanation:

What is the solution to the equation 3x+1-6x=72-example-1
User Jack Dempsey
by
6.1k points